The Influence of Experiential Quality on Revisit Intention at Goa Batu Kapal Tourist Attraction South Solok District - Arif Syafri Weldy; Feri Ferdian (Lembaga Pengembangan Kinerja Dosen, 2024)
This study discusses how experiential quality affects revisit intention at the Goa Batu Kapal tourist attraction in South Solok Regency, which is motivated by the number of visits that have experienced instability and decline in the last 6 months, In pre-research, we found that 70% of people who visited us may not want to revisit again. Some people also left negative comments on google reviews. about the Goa Batu Kapal tourist attraction in South Solok Regency. This study employed a purposive sampling technique, which yielded 199 samples, along with a quantitative method using a causal associative approach as the research methodology. A questionnaire with a Likert scale arrangement that has undergone validity and reliability testing is used in the data gathering method. The R-squared results indicate that, with a percentage value of 69.3%, experiencing quality has a significant impact on revisit intention, with other factors accounting for the remaining 30.7%. The results of this study show that the experiencing quality variable has a significant impact on revisit intention, with the hypothesis testing yielding a t-statistic 16.6> 1.96 and a p value 0.00 <0.05. The study concludes that whereas Ho is rejected, Ha is accepted.